Cytological Criteria for Predicting the Luminal Phenotype of Breast Carcinoma - Paschoalini, Rafael Bispo [UNESP]; Dufloth, Rozany Mucha [UNESP]; Moraes Neto, Francisco Alves; Schmitt, Fernando C. (Karger, 2016)
Background: Specific cytological criteria for the luminal phenotype of breast carcinoma, despite it being the most common and having a better prognosis as well as targeted therapies under study, remain to be established. Using fine-needle aspiration cytology (FNAC), we aimed to identify the luminal phenotype through the evaluation of cytological criteria recognized in routine practice. Methods: We correlated 169 FNACs of breast carcinomas with their tissue specimens, classified into phenotypes by immunohistochemistry (applying tissue microarray technology) as luminal A, luminal B, HER2 overexpression, and triple negative. All FNAC samples were blindly reviewed according to cellularity, cell cohesion, necrosis, nucleoli, and nuclear atypia. Fisher's exact test was used to test associations between the cytological criteria and phenotypes. Results: The following phenotypes were obtained-luminal A: 107 (63.3%), luminal B: 39 (23.1%), HER2 overexpression: 8 (4.7%), and triple negative: 15 (8.9%). The luminal phenotype showed mild/moderate cellularity (40.4%) (OR = 7.12, 95% CI: 1.61-31.52), inconspicuous, present nucleoli (55.5%) (OR = 8.31, 95% CI: 2.36-29.19), and mild/moderate nuclear atypia (44.5%) (OR = 8.42, 95% CI: 1.90-37.25). Conclusion: The criteria that might indicate the luminal phenotype of breast carcinoma in FNAC were mild/moderate cellularity, inconspicuous, present, and nonprominent nucleoli, and mild/moderate nuclear atypia. (C) 2016 S. Karger AG, Basel.
Keywords: Breast carcinoma; Cytological criteria; Cytopathology, breast; Fine needle aspiration cytology; Luminal phenotype; Molecular classification